Women of valor : Orthodox Jewish troll fighters, crime writers, and rock stars in contemporary literature and culture - Skinazi, Karen E., 1974- (Rutgers University Press, 2018)
Media portrayals of Orthodox Jewish women frequently depict powerless, silent individuals who are at best naive to live an Orthodox lifestyle, and who are at worst, coerced into it. Skinazi delves beyond this stereotype to identify a powerful tradition of Jewish women's feminist portrayals of Orthodox women in literature, film, and music.
Keywords: Jewish women -- Religious life.; Jewish women in popular culture.; Orthodox Judaism.; Popular culture -- Religious aspects -- Judaism.; Juives -- Vie religieuse.; Judaïsme orthodoxe.; Culture populaire -- Aspect religieux -- Judaïsme.; RELIGION -- General.; Jewish women in popular culture; Jewish women -- Religious life; Orthodox Judaism; Popular culture -- Religious aspects -- Judaism; Electronic books.